Social Capital and Neighborhood Security in Emirates Society: A Sociological Study on a Sample of Sharjah Neighborhoods - Algharbawi, Fatima; Alhourani, Mohammed; Nashwan, Ayat (Dirasat: Human and Social Sciences, 2024)
Objectives: The study aims to reveal the security of neighborhoods in the UAE society by focusing on physical preventive security dimensions through social capital networks in the neighborhoods of the Emirate of Sharjah. Methods: The study relied on a quantitative approach through a social survey on a clustered random sample of the total areas in the Emirate of Sharjah. A questionnaire was distributed to 500 male and female Emirati citizens residing in the following areas: Al-Mawafajah, Al-Rahmaniyah, Al-Zahiyah, the central region, and the eastern coast. Results: The results show that social capital is an essential pillar of physical preventive security, as it was found that the network of social relations in the Emirate of Sharjah, and its production circles continuously for mixed neighborhoods. The prominent dimensions of neighborhood security include: First, utilitarian security represented in material aid and the issued decision. Second, real estate security, represented by no fear for belongings and safety at home. Third, health security, represented by communication contributing to disease prevention and knowledge of different doctors. Fourth, environmental security, which involves solving sewage problems and ensuring the safety of public. Conclusion: The study confirms that the network of social relations in the neighborhood provides physical preventive security for citizens in non-mixed neighborhoods. This indicates the flow of social capital indicators within the dimensions of physical preventive security and its direct impact on individuals’ feelings and security status and reflects the extent of the success of the approach imposed by the state. The representation of the tribe and the neighborhood is the primary source of security before going out to legal and security institutions.